2014
DOI: 10.1016/j.jallcom.2014.03.145
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of mixed α/β-SiAlON powders via salt-assisted combustion synthesis

Abstract: High-quality Y-and Ca-α/β-SiAlON and α-SiAlON ceramics were synthesized via salt-assisted combustion synthesis from Si, Al, and metal oxide (Y 2 O 3 and CaO) with the addition of NaCl and MgCl 2 under a nitrogen pressure of 1 MPa. NaCl and MgCl 2 were employed as they act as excellent diluents that effectively absorb the reaction heat through melting and evaporation. We found that the type of metal chlorides employed significantly affected the α/β ratio and the morphology of the product, with the use of NaCl a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…In contrast, the Ca0.3M18 and Y0.2M18 samples obtained with the addition of 18 mass% MgCl 2 exhibit much lower α-phase SiAlON contents of 7% and 56%. These results are consistent with our previous work, which showed that NaCl is more efficient at promoting the formation of α-phase SiAlON [12]. It should be noted, however, that these values are only approximate, as any amorphous phase fractions cannot be determined precisely using this method.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, the Ca0.3M18 and Y0.2M18 samples obtained with the addition of 18 mass% MgCl 2 exhibit much lower α-phase SiAlON contents of 7% and 56%. These results are consistent with our previous work, which showed that NaCl is more efficient at promoting the formation of α-phase SiAlON [12]. It should be noted, however, that these values are only approximate, as any amorphous phase fractions cannot be determined precisely using this method.…”
Section: Resultssupporting
confidence: 92%
“…In previous work, 12 mass% NaCl and 18 mass% MgCl 2 addition was needed to achieve complete nitridation of Si in the salt-assisted combustion synthesis of α/β-SiAlON [12]. Based on this, the same amounts of NaCl and MgCl 2 were added to the reactant powders in the present study.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In these studies, NaCl was shown to decrease the adiabatic temperature and wave velocity, stabilizing the combustion reaction, and thereby reducing the rate of aggregation and grain growth. Our previous work [22][23][24] on the combustion synthesis of SiAlON has shown that metal chlorides such as NaCl, KCl, and MgCl 2 are ideal diluents that absorb the reaction heat effectively via their sensible and latent heats, thereby lowering the combustion temperature. In addition, different morphologies were obtained in the products according to the type and amount of metal chloride used.…”
Section: Introductionmentioning
confidence: 99%